Análise do perfil da expressão de genes candidatos com a eficiência alimentar de animais da raça Nelore - Rosa, Kamila de Oliveira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Brazil is one of the leading producer and exporter of meat. However, different livestock and plant production have been competing with cattle for space and importance in Brazilian trade balance. Thus, the animal breeding has played a key role in beef cattle to increase production levels occupying the same space at lower costs. Feed efficiency is a productive trait of extreme importance, but it has not been considered in genetic evaluation programs in our country. This is probably due to the fact that the measurement is costly and late. In this scenario molecular genetics may contribute to the implementation of this trait in breeding programs by identifying candidate genes for feed efficiency. The present study aimed to confirm the differential gene expression levels of candidate genes previously identified by RNA sequencing (RNA-seq) in extreme groups of animals evaluated for feed efficiency. We adopted the real time quantitative PCR methodology (qPCR) to verify a quantitative relationship between the level of gene expression and feed efficiency in an experimental population of 83 Nelore cattle evaluated for different feed efficiency traits. A subgroup composed of 20 animals extreme for Residual Feed Intake (RFI) was evaluated for overall standard of expression by RNA-seq technology to identify genes differentially expressed (DE). From the identified DE genes six candidate genes were selected (PPP1R26, FABP1, FADS2, RGS2, SLC2A5 and UCP2) based on fold change values and its metabolic function related to feed efficiency. The qPCR analyses were performed to confirm association between the expression level of the six target genes with measures of feed efficiency. It was observed association between the FABP1 gene with residual feed intake and dry matter intake (P <0.05). Also, the SLC2A5 gene was associated with Kleiber index measurements and relative growth rate (P <0.05). In both cases an increase in the expression level was associated ...

O Brasil se consolidou como um dos principais produtores e exportadores mundiais de carne. Entretanto, diversas culturas (animal/vegetal) têm competido com a bovinocultura por espaço e importância na balança comercial brasileira. Assim, o melhoramento genético animal tem tido, no Brasil, papel fundamental na pecuária de corte de forma a manter crescentes os níveis de produção ocupando o mesmo espaço e a baixo custo. A eficiência alimentar é uma característica produtiva de extrema importância, porém não está sendo considerada nos programas de avaliação genética no país, devido ao fato de a mensuração ser onerosa e tardia. Nesse cenário a genética molecular pode contribuir para a implementação da seleção dessa característica em programas de melhoramento por meio da identificação de genes importantes para eficiência alimentar. O presente estudo objetivou comprovar o padrão de expressão de genes diferencialmente expressos previamente identificados por sequenciamento de RNA (RNA-seq) em animais extremos para eficiência alimentar. Nesse contexto foi adotada a metodologia de PCR quantitativo em tempo real (qPCR) a fim de estabelecer uma relação quantitativa entre nível de expressão gênica e a eficiência alimentar em uma população experimental de 83 animais da raça Nelore avaliados para diferentes medidas de eficiência alimentar. Um subgrupo composto por 20 animais extremos para o consumo alimentar residual (CAR) foi avaliado quanto ao padrão de expressão global pela tecnologia de RNA-seq para identificação de genes diferencialmente expressos (DE). A partir dos genes DE identificados foram selecionados seis genes candidatos (PPP1R26, FABP1, FADS2, RGS2, SLC2A5 e UCP2) com base nos valores de Fold Change e sua função metabólica para a característica em estudo. As qPCR foram realizadas para identificar associações entre o nível de expressão dos seis genes alvo com as medidas de ...
Keywords: Bovino de corte; Nelore (Zebu); Bovino - Eficiencia alimentar; Expressão gênica; Genetica animal; Gene expression